Does the use of indirect calorimetry change outcome in the ICU? Yes it does. Issue 2 (March 2018) - De Waele, Elisabeth; Honoré, Patrick M.; Malbrain, Manu L.N.G.
Abstract : Purpose of review: To review the recent findings on metabolic monitoring and possible beneficial effects of an adequate nutrition therapy, based on indirect calorimetry as the golden standard to predict energy expenditure. Recent findings: in the last decades, major steps are taken in the field of metabolism and nutrition, evolving from nutrition as a baseline support to a therapeutic intervention. The aspect of energy expenditure is of cardinal importance, and technical possibilities have impressively improved: from the first 'calorimetre' in 1789 to the new generation, clinical applicable indirect calorimeters and the high accuracy and easy use model reaching high technology readiness level [Oshima et al. (2017). Clin Nutr 36:651]. Several recent studies provide information on the technique of metabolic monitoring itself and the positive effects of implementation of the tool in a high-end nutritional care plan [Oshima et al. (2017). Clin Nutr 36:651]. The combination of correct energy provision and protein prescription has shown benefits, and mortality of ICU patients is related to the amount of energy provided [Zusman et al. (2016). Crit Care 20:367]. The use of a monitor per se will not change outcome. Optimal dosing of artificial nutrition can be achieved by the use of a parameter acquired by a measurement instead of by inaccurate equations. In the era of precision medicine, this approach has shown positive effects on outcome. Moreover, above all, the concept of metabolic monitoring of the critically ill is just an issue of common sense. Summary: Metabolic monitoring by indirect calorimetry is achieving a level in which it can be implemented in critical care practice. Evidence is available to prove that by guiding your nutritional therapy by measured values, it will change outcome of critically ill patients.